BENTHIC FORAMINIFERA AS INDICATORS OF PALEOECOLOGICAL BOTTOM CONDITIONS IN THE SERRAVALLIAN TREMITI SECTIONS (EASTERN MEDITERRANEAN, ITALY) (Rivista italiana di Paleontologia e Stratigrafia, 2002)
Quantitative analysis of  benthic foraminifera from the Serravallian S. Nicola composite section (Tremiti Islands, Adriatic Sea) and about 37 m thick, pointed out changes of bottom paleoecological conditions in this eastern Mediterranean area during the analyzed time interval. Benthic foraminiferal assemblages are typical of bathyal environment and indicate a constant paleobathymetry of about 1,000 m. Changes in benthic foraminiferal assemblages allowed us to identify five intervals,  which were calibrated on the astrochronological scale to reconstruct paleoecological evolution of bottom conditions. In particular starting from the base of the section the following different bottom conditions have been identified: 1) between about 12.62  to about 12.29 Ma high surface productivity, active bottom water circulation and, consequently, moderate bottom food supply; this paleoenvironment slightly changed  between about 12.49 and 12.29 Ma, where benthic assemblages testify unstable bottom conditions with periods of active circulation (relative abundance of Cibicidoides wuellerstorfi), alternated with periods of sluggish circulation  (peaks of Bulimina subulata group); 2) relatively oxygenated paleoenvironment together with low food supply between about  12.29 - 12.08 Ma; 3) increase of organic matter content (abundance of  U. peregrina-pygmaea), due to higher surface productivity and/or greater preservation of organic matter at bottom from 12.08 to 11.81 Ma; 4) relatively oxygenated conditions with low food supply from 11.81 to about 11.45 Ma; 5) similar conditions to those of the basal part (about 12.62  - 12.29 Ma) of the section from about 11.45 to 11.10 Ma, but with an increase of organic matter content. Finally, the comparison between the paleoecological reconstruction of the S. Nicola composite section and Ras il-Pellegrin (Malta) composite section (reported in this volume) in  the interval between about 12.6 and 12.2 Ma, pointed out very different extimated paleobatimetries, but similar paleoecological bottom conditions with evidence of relative high productivity.